Find the zero of the polynomial in both of the following cases :

Asked by shrey17 | 5th Apr, 2009, 04:11: PM

Expert Answer:

1) p(x)=0 implies ax=0

 but a is non zero , so x=0

 So, the value of x=0 takes p(x) =0 so x=0 is the zero of p(x)

2) simly,

p(x)=0 implies cx+d=0

So we get

x=-d/c..(c is non zero, so division by c is possible)

 So  the value of x=-d/c  takes p(x) in this case equal to zero.

So, x=-d/c is the zero of p(x)

Answered by  | 5th Apr, 2009, 04:28: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.